Pengaruh Leader Member Exchange Terhadap Kepuasan Kerja Melalui Perceived Organizational Support Pada Perusahaan Daerah Pasar Kota Medan - Dhea Annisa Lubis (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2022)
This study aims to determine the effect of leader member exchange on job satisfaction. To determine the effect of leader member exchange on perceived organizational support. To determine the effect of perceived organizational support on job satisfaction. To determine the effect of leader member exchange on job satisfaction through perceived organizational support. The total population in this study amounted to 700 people, and the samples taken were 88 people using the slovin method. The analysis technique used is path analysis. The results show that leader member exchange has a positive and significant effect on employee job satisfaction, leader member exchange has a positive and significant effect on perceived organizational support, perceived organizational support has a positive and significant effect on employee job satisfaction and leader member exchange has a positive and significant effect on job satisfaction. through perceived organizational support.